Reframing culture: Stuart Cunningham's legacies. (February 2022) - Thomas, Julian
This essay offers an appreciation of Stuart Cunningham's substantial and diverse contributions to 'reframing culture' in Australian research, policy and industry practice, from his early reformulations of Australian film history to his recent work on digital media disruption. The essay discusses the range of Cunningham's institutional and intellectual legacies, suggesting that his advocacy for cultural policy and the creative industries together with his leadership of major collaborative research initiatives in the humanities and social sciences have been especially important for media and cultural studies in Australia. Further, his approach to the project of 'reframing culture' is likely to remain a critical task.